Secondary school students’ English literacy achievement based on PISA reading literacy test 2009 - Mirizon, Soni; Vianty, Machdalena; Rosmalina, Ida; Erlina, Erlina (Englisia Journal, 2021)
Reading literacy has become global concern that Organisation for Economic Co-operation and Development (OECD) has conducted Program for International Student Assessment (PISA) reading literacy test to assess what students know and can do in reading. Participating in PISA test since 2000, Indonesian students’ reading literacy has not shown a significant improvement. Because PISA reading literacy test is adapted into language of instruction of each participating country, it is Indonesian students’ reading literacy in Indonesian language which is not satisfactory. Considering the fact that Indonesian fifteen-year-old students study English as a compulsory subject, investigating students’ reading literacy in English is considered important. There has been much research investigating issues in reading achievement in Indonesia, but there are limited studies focussing on PISA reading literacy based on school location, school accreditation, gender, and academic major. Employing survey study design, this study assessed reading literacy of two thousand and two hundred secondary school students sampled from twenty four public secondary schools accredited A+, A, and B in Palembang. Data were obtained using PISA reading literacy test 2009 and were analysed statistically. The findings revealed that students’ English literacy was in level 3 (low category). Students studied at schools in central urban district performed better than those of in peri urban district. Those from secondary schools accredited A+ outperformed their counterparts in schools accredited A and B. Female students performed slightly better than male. Students majoring in science were better than those of majoring in social. The results lead to the conclusion that students’ English literacy achievement should be enhanced using innovating strategies to achieve targeted literacy level that is needed to survive in school academic life.